The Influence of Religiosity and Social and Psychological Factors on Purchase Decisions and Consumer Loyalty - Ginting, Yanti Mayasari; Handriano, Rory; Sutomo (Indonesian Journal Economic Review (IJER), 2025)
This study is based on the impact of religiosity, data from social aspects, psychological factors influence how to make a purchase or what influences consumer perception and brand loyalty.In a competitive market, companies need to understand these various influences in order to draw up new marketing strategies.Religious motivation is also very important in buying decisions, for example this thing "ill-gotten gains" has nothing to do with me.Social factors, such as the use which the household makes of a product, or finder fees for finding suppliers, can also affect consumer evaluations.Meanwhile, psychological factors, such as motivation, perception and affect also run through consumer decisions.The results show that religiosity does have a significant positive effect on buying decisions purely speaking of purchase power However, psychological factors have a profound impact on consumer loyalty, from many variables but nevertheless through this wide array have an enormous impact relative to results for other study samples. The report concludes that social aspects significantly influence a firm's consumer loyalty; however they do not have this kind of impact on purchasing decisions.These findings shed new light on the way in which both internal and external factors can shape consumer behavior.Companies will find it easier then to devise solutions that more easily interest or satisfy the consumer, thus increasing customer loyalty while enabling them to maintain their footing in the market.